Emerging Technologies and Innovative Education in Secondary Schools for Job Creation in Anambra State, Nigeria - Martha-Rose Ifeoma Uwaezuoke (LPPM STKIP Kusuma Negara, 2023)
The study which assessed emerging technologies and innovative education in secondary schools for job creation in Anambra State, Nigeria was guided by two research questions adopted descriptive survey research design. The population of the study consists of all the teachers in the 264 secondary schools numbering about 4,370. Cluster random sampling technique was used to select 1,504 teachers for the study. The instrument was self-designed and entitled â€œEmerging Technologies Innovative Education Questionnaireâ€ (ETIEQ). The validity of the instrument was ensured. Test retest method was used to ascertain the reliability of the instrument and the scores were subjected to Pearson Moment Correlation Coefficient which gave rise to 0.79 which is adjudged reliable. Simple percentage was used for data analysis to answer the research questions. The findings revealed but not limited to: that teachers in secondary schools are not aware of some of the essential emerging technology tools. It is therefore recommended among others that the government and other relevant authorities should expedite action and begin awareness campaign by installing these facilities to schools for use to enable the recipients be job creators and self-reliant upon graduation in many entrepreneurship enterprises thus a greater Nigeria.